Preparing Test Blueprints or "Grids" - Christopher Reznich; Dianne P. Wagner (Association of American Medical Colleges, 2013)
Abstract This self-instructional module on test blueprinting provides the user with basic instruction on the rationale for and process of creating test blueprints. A test blueprint, also called a table of specifications, is a grid that represents the numbers of test items and their distribution across content objectives. A test blueprint helps ensure appropriate item representation on a test in relation to the emphasis placed on specific objectives by the instructor and that no important content is missed. This module and its associated instructor's guide present rationales for creating test blueprints, examples, and an easy-to-follow process for test blueprint creation. Analysis of test blueprints for purposes of exam improvement is also addressed. The module running time is 7 minutes and 19 seconds. While it is difficult to specify clearly how much time should be spent creating test blueprints, it is the authors' experience that this activity takes on the order of 1-2 hours, depending upon the amount of discussion needed to refine the blueprint by contributing faculty. The resource has been successfully implemented for 3 years with no reports of problems. Faculty comments indicate that it is easy to use, informative, and technologically reliable.